Source country-specific burden on health due to high concentrations of PM2.5 - Lim, Youn Hee; Kim, Soontae; Han, Changwoo; Bae, Hyun Joo; Seo, Sung Chul; Hong, Yun Chul (Environmental Research, 2020)
Asian countries face frequent spikes in concentrations of particulate matter smaller than 2.5 μm (PM2.5), which may consist of domestic emissions, transported pollutants from neighboring countries, and secondary aerosol formation (SAF). We aimed to estimate the burden on health in South Korea due to PM2.5 exposure from source countries. We computed the health benefits of meeting air quality guidelines during high pollution periods or spike periods. We used daily mortality counts, PM2.5 concentrations, and primary and secondary contributions to pollutant levels in seven cities and nine provinces in South Korea during 2006–2016. Generalized additive mixed modeling with a Poisson distribution and random effects in 16 regions was used to examine the short-term effects of PM2.5 on mortality. We computed attributable burden due to PM2.5 exposure and the potential benefits of meeting the air quality guidelines set by the World Health Organization (WHO, 25 μg/m3) and the Korea Ministry of Environment (50 and 35 μg/m3 before and after 2015, respectively). A concentration–response curve showed a non-linear relationship between daily mortality counts and PM2.5 levels. The short-term health impacts of PM2.5 were suggested to be 1638 non-accidental deaths in 2016 in South Korea due to daily domestic emissions and pollutants transported from neighboring countries. Of these, 1509, 995, or 238 deaths could have been prevented if the daily mean PM2.5 concentration had been kept below 25, 35, or 50 μg/m3. After accounting for the contribution of SAF to PM2.5, primary sources of PM2.5 resulted in 258–860 and 26–88 deaths due to pollution transported from China and North Korea, respectively, and 162–538 deaths were due to domestic emissions. Meeting the air quality guidelines of the WHO could have prevented most of these deaths.
Keywords: Air Pollutants; Air Pollution; Asia; China; Cities; Environmental Exposure; Environmental Health; Humans; Particulate Matter; Republic of Korea; Attributable mortality; Health impact assessment; Particulate matter; Short-term effects; Transboundary air pollution